Rate dependent mode II traction separation law for S-2 glass/epoxy interface using a microdroplet test method. (September 2019) - Tamrakar, Sandeep; Ganesh, Raja; Sockalingam, Subramani; Gillespie, John W.
Abstract: This paper presents a methodology to determine unique Mode II rate dependent traction separation law for composite interfaces by simulating all of the physically observed mechanisms in S glass fiber/epoxy microdroplet experiments conducted over a wide range of loading rates (1 µm/s to 1 m/s). A unique set of traction separation laws were determined for each loading rate by narrowing down the range of traction law parameters that accurately predicts interfacial shear strength (IFSS) with the correct failure mode for different droplet sizes (75 to 125 um). Peak traction and the fracture energy increase with the increase in the rate of loading by a factor of 1.9 and 3, respectively. The simulation provides insight into the importance of accurate rate dependent peak traction stress and resin yield stress as this ratio governs the failure mechanisms associated with IFSS and energy absorption during the debonding process.